ACTION GAMES ARE A FACTOR THAT INCREASES THE PHYSICAL FITNESS AND HEALTH OF GIRLS (American Journal of Interdisciplinary Research and Development, 2022)
This article talks about the fact that action games are one of the important factors that increase the physical fitness and health of girls.